Pengaruh Corporate Governance, Kepemilikan Institusional, Leverage dan Growth terhadap Tingkat Materialitas Sustainability Report - Elan Kurniawan; Rani Astuti (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
The research aims to determine the influence of Corporate Governance, institutional ownership, Leverage and Growth of the industry level of Sustainability Report. The theory in this study uses the legitimation theory, which confirms that the company continues to strive to ensure that it performs in accordance with the frames and norms in the society and Environment in which the company resides, the sample uses the Purposive sampling method. The results of the research in the financial sector showed that Corporate Governance positively and significantly affect the level of materiality of the Sustainability report industry economic aspects, Leverage positive and significant impact on the level of Sustainability report industry aspects of economic performance, environmental performance and social performance. The results of the research in non-financial sector companies show that Corporate Governance positively and significantly affects the level of materiality of the Sustainability report industry environmental performance and negatively and significantly impact on The materiality level of Sustainability report industriality of economic performance, Growth affects positively and significantly to the level of materialities of the Sustainability report industry aspects of economic performance, environmental performance and social performance.